STRATEGY ANALYSIS FOR COWORKING SPACE OPERATOR TO SUSTAIN IN INDONESIAN MARKET - Rengganis, Kharisma
Coworking considered as a disruption in the way people work. Traditionally, people would work in an office space provided by the company they work for, where they will work side by side with peers from the same company. Nowadays, some company would opt to rent a small size areas or even a single desk for their employee to work, where they will work side by side with people from other company. Coworking space operator business is to lease a large size office space from the building owner and then sublease the space in small sizes to other company. The main customer of a coworking space are startups or freelancer, where they get the benefit of a fully equipped low cost office space that can be rented in short period, whether on monthly basis or daily basis. The office layout usually unlike a traditional office space, where there would be a game room as well as a comfortable couches and bean bags. Since the people that is working in a coworking space are coming from different companies, coworking space operators would encourage the connection between the members, such as by organizing a gathering or facilitate a forum for the members to interact. The community in a coworking space is the most important factor that differentiate a coworking space with other place to work such as coffeeshops, home, or a traditional office space. It should be the main factor that will attract new member and retain current member. Based on the research, it can be concluded that coworking space industry has a potential to continue to grow in the future. The demand for coworking space will continue to grow and the government is supporting the industry. However, to be able to sustain in Indonesian market, coworking space operator need to develop a competitive advantage, which currently is lacking. It needs to develop resources and capabilities that will support the company in achieving superior performance compare to its competitors. Especially since the research also shows that the company’s profitability will be under pressure due to tough competition, potential rising costs, and choosy customers that can easily switch to other coworking space or other alternative place to work.